Anaerobic treatment of residual lemon pulp in digesters with semi-continuous feed. - Navarro, A. R. (Water Science and Technology)
Lemon growing areas in the north of Argentina have industries that produce concentrated juice, peel and essential oil and generate a significant amount of liquid and solid waste as lemon pulp. In Argentina, despite the potential applications that the pulp has as animal feed and human and industrial raw material, only 10% is used for these purposes and the rest is discarded into the environment causing many ecological and economic problems. There is little information in the literature on biotechnologies for the treatment of this industrial waste. This paper shows that lemon pulp is a suitable substrate to be treated by anaerobic digestion. We obtained 86 and 92% reduction of chemical oxygen demand in a digester with a semi-continuous feed and retention time of 10 and 20 days respectively and a productivity of 0.406 g CH4/g VS h. Comparative tests showed that pre-digesting the pulp improved the process of digestion and increased biogas generation by 20%.